Wykorzystanie wielorównaniowych modeli AR-Garch w pomiarze ryzyka metodą VaR - Piontek, Krzysztof; Papla, Daniel (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In this paper an example of utilizing multi equations AR-GARCH models in measuring risk of two elements portfolio using a variation - covariation method is presented. This modern - conditional - approach was compared with more classic, non-conditional method, which assumes that parameters of multidimensional density function are constant in time.In first part of this paper few essential concepts related to VaR and its measurement using variance-covariance matrix are introduced. In second part two models of returns and methods of calculating vector of conditional means and conditional variance-coviariance matrix are presented, one model is non-conditional, second is a multidimensional AR-GARCH model. Then tests of goodness of VaR models are presented. Empirical example, in which data from chosen worlds and Polish capital markets were used, concludes the paper. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 126-138